2004
DOI: 10.1523/jneurosci.5191-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Deletion of Mossy Cells Does Not Result in a Hyperexcitable Dentate Gyrus: Implications for Epileptogenesis

Abstract: Loss of cells from the hilus of the dentate gyrus is a major histological hallmark of human temporal lobe epilepsy. Hilar mossy cells, in particular, are thought to show dramatic numerical reductions in pathological conditions, and one prominent theory of epileptogenesis is based on the assumption that mossy cell loss directly results in granule cell hyperexcitability. However, whether it is the disappearance of hilar mossy cells from the dentate gyrus circuitry after various insults or the subsequent synaptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
91
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 55 publications
12
91
1
3
Order By: Relevance
“…Hyperexcitability of the hippocampal dentate gyrus has been described in the popular lateral fluid percussion injury model of closed head injury in the rat and potentially attributed to alterations in hippocampal circuitry (Lowenstein et al, 1992;Coulter et al, 1996;Toth et al, 1997;Santhakumar et al, 2000Santhakumar et al, , 2001. Cytoarchitectual changes as demonstrated by selective hilar neuronal loss (Lowenstein et al, 1992;Toth et al, 1997;Santhakumar et al, 2000Santhakumar et al, , 2001 and mossy fiber sprouting (Santhakumar et al, 2001) have been shown and associated with dentate granule cell hyperexcitability, although some recent studies refute this hypothesis (Ratzliff et al, 2004). Larger, longer-lasting multiphasic field potential have been recorded from the hippocampus of animals after TBI compared to field potentials in controls (Santhakumar et al, 2000(Santhakumar et al, , 2001Akasu et al, 2002;Coulter et al, 2002).…”
Section: Traumatic Brain Injury-induced Spontaneous Recurrent Seizuresmentioning
confidence: 99%
“…Hyperexcitability of the hippocampal dentate gyrus has been described in the popular lateral fluid percussion injury model of closed head injury in the rat and potentially attributed to alterations in hippocampal circuitry (Lowenstein et al, 1992;Coulter et al, 1996;Toth et al, 1997;Santhakumar et al, 2000Santhakumar et al, , 2001. Cytoarchitectual changes as demonstrated by selective hilar neuronal loss (Lowenstein et al, 1992;Toth et al, 1997;Santhakumar et al, 2000Santhakumar et al, , 2001 and mossy fiber sprouting (Santhakumar et al, 2001) have been shown and associated with dentate granule cell hyperexcitability, although some recent studies refute this hypothesis (Ratzliff et al, 2004). Larger, longer-lasting multiphasic field potential have been recorded from the hippocampus of animals after TBI compared to field potentials in controls (Santhakumar et al, 2000(Santhakumar et al, , 2001Akasu et al, 2002;Coulter et al, 2002).…”
Section: Traumatic Brain Injury-induced Spontaneous Recurrent Seizuresmentioning
confidence: 99%
“…One possibility is that CCh causes a dramatic increase in quantal content, although a competing explanation is that CCh promotes synchronous release from somatic and perisomatic GABAergic inputs. Although we did not perform experiments aimed directly at this question, both early speculation and more recent experimental work in area CA1 favors the latter hypothesis (Alger et al 1996;Reich et al 2005).…”
Section: The Role Of Muscarinic Acetylcholine Receptors In Dsimentioning
confidence: 87%
“…These cells are unique among local circuit neurons in the hippocampus and dentate gyrus in that they are glutamatergic rather than GABAergic (Scharfman 1995). They are also extremely sensitive to both ischemia and excitotoxicity (Freund and Magloczky 1993;Hsu and Buzsaki 1993;Magloczky and Freund 1993), have a strong longitudinal projection (Amaral 1978;Amaral and Witter 1989;Buckmaster and Schwartzkroin 1994;Buckmaster et al 1992), and have been consistently implicated (through either their loss or dysfunction) in several competing theories on the etiology of temporal lobe epilepsy (Houser 1999;Lothman et al 1996;Ratzliff et al 2002Ratzliff et al , 2004Santhakumar et al 2000;Sloviter 1991). Our results indicate that excitation of hilar mossy cells produces a robust inhibition of local GABAergic transmission and suggest a prominent role for EC-dependent retrograde signaling in hilar neurophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative, albeit not mutually exclusive, possibility is that the SGC IML associational collaterals may excite neighboring granule cells, forming a local focus of hyperexcitability after trauma. SGC innervation of surviving mossy cells (Williams et al, 2007) may also contribute to septotemporal spread of excitability (Ratzliff et al, 2004). Given the typical sustained SGC firing, the possibility that SGCs drive early postinjury increases in dentate excitability is compatible with the contribution of polysynaptic network activity to the increase in duration of granule cell and mossy cell firing after brain injury (Santhakumar et al, 2000).…”
Section: Discussionmentioning
confidence: 99%